Prevalence of sleep-disordered breathing in an African general population: The Benin Society and Sleep (BeSAS) study. Issue 9 (September 2022) - Wachinou, Ablo Prudence; Houehanou, Corinne; Ade, Serge; Totah, Terence; Berger, Mathieu; Solelhac, Geoffroy; Amidou, Salmane; Fiogbe, Attanon Arnauld; Alovokpinhou, Frederic; Lacroix, Philipe; Preux, Pierre-Marie; Marques-Vidal, Pedro; et al.
Summary: Background: Data on the prevalence of sleep-disordered breathing (SDB) in the African general population are scarce, and a better understanding is urgently needed. Our study aimed to objectively determine the prevalence of, and factors associated with, SDB in a large sample in Benin, west Africa. Methods: In the Benin Society and Sleep (BeSAS) cross-sectional study, participants aged 25 years and older were recruited from both urban and rural areas. Rural participants were recruited from Tanve, a village located 200 km north of Cotonou, and urban participants were recruited from Cotonou. The participants underwent respiratory polygraphy at home using a type-3 device that measures airflow through a nasal pressure sensor, respiratory effort (thoracic movement), and pulse oximetry. Clinical and morphometric data were also collected. SDB severity categories were defined according to the apnoea–hypopnoea index (AHI), with mild-to-severe SDB (AHI ≥5/h), moderate-to-severe SDB (AHI ≥15/h), and severe SDB (AHI ≥30/h). Findings: The study was completed from April 4, 2018 to Jan 15, 2021. Of 2909 participants recruited in the BeSAS study, 2168 (74·5%) underwent respiratory polygraphy. For the 1810 participants with complete polygraphic data (mean age 46 years, SD 15; 1163 [64·2%] women), the prevalence of mild-to-severe SDB (AHI ≥5/h) was 43·2% (95% CI 40·9–45·5), of moderate-to-severe SDB (AHI ≥15/h) was 11·6% (10·2–13·1), and of severe SDB (AHI ≥30/h) was 2·7% (2·0–3·5). Factors independently associated with SDB were advanced age, male sex, large neck circumference, abdominal obesity, overweight or obesity, and snoring. After multivariable adjustment, severe SDB was independently associated with hypertension in women (odds ratio 3·99, 95% CI 1·04–15·33; ptrend =0·044), but not in men (odds ratio 0·67, 0·22–2·05; Ptrend =0·63). Interpretation: The BeSAS study provides the first large-scale objective evaluation of SDB prevalence and associated factors in Africa. The high prevalence of SDB identified should stimulate the development of public health policies to prevent and treat this condition in African countries. Funding: Ligue Pulmonaire Vaudoise, Switzerland.